Podoba govorjenega slovenskega knjižnega jezika v Slovenskem pravopisu 2001 - Tivadar, Hotimir (Slavistična revija, 2003)
The article discusses the issues of spoken literary language, as is evident from the newest codifying reference work, Slovenski pravopis 2001. This, by its name orthographic, reference work with its rules and dictionary specifically concerns also spoken literary language, i.e., from the orthografic as well as the broader, phonetic-phonological, aspect. The basic intention and the reason for this article was the vagueness in the realization of spoken literary language vis-a-vis the norm. Of a particular interest was the definition and function of the spoken literary language in the contemporary Slovene studies, phonetic-phonological description of literary language in the chapter "Glasoslovje" ohonology. A special emphasis was placed on the topical and realistic nature of the literary norm.
Keywords: fonemi; fonetika; knjižni jezik; phonetics; pravorečje; Slovene; Slovenski pravopis; slovenščina; standard language